Quantitative trait loci for partial resistance to Pseudomonas syringae pv. maculicola in Arabidopsis thaliana. (3rd June 2013) - Rant, Jenni C.; Arraiano, Lia S.; Chabannes, Matthieu; Brown, James K. M.
Summary: Segregation of partial resistance to Pseudomonas syringae pv. maculicola ( Psm ) ES4326 was studied in the recombinant inbred population created from accessions (ecotypes) Columbia (Col‐4), the more susceptible parent, and Landsberg (Ler‐0). Plants were spray inoculated with lux‐transformed bacteria in experiments to measure susceptibility. The amount of disease produced on a range of Col × Ler lines by spray inoculation was highly correlated with that produced by pressure infiltration of bacteria into the apoplast. Quantitative trait locus (QTL) analysis identified four loci that contributed to partial resistance: QRps.JIC‐1.1, QRps.JIC‐2.1, QRps.JIC‐3.1 and QRps.JIC‐5.1 on chromosomes 1, 2, 3 and 5, respectively . QRps.JIC‐3.1, located 8.45 cM from the top of the consensus genetic map of chromosome 3, had a large, approximately additive effect on partial resistance, explaining 50% of the genetic variation in this population. Fine mapping narrowed the region within which this QTL was located to 62 genes. A list of candidate genes included several major classes of resistance gene.